Cooperative Business Competitiveness Model Based on Business Type in Palu City - Parani, Syamsul Bahri Dg.; Syamsuddin, Syamsuddin; Ponirin, Ponirin; Sukardi, Sukardi (Ridwan Institute, 2025)
The advancement of science and technology has intensified global economic competition, often marginalizing community-based economic systems, such as cooperatives. Despite their constitutional role as pillars of Indonesia’s national economy, cooperatives in Palu City struggle with internal and external challenges, weakening their competitiveness. While prior studies have examined cooperative strategies generically, this research introduces novelty by developing type-specific competitiveness models for savings and loan, service, consumer, and producer cooperatives in Palu City, integrating SWOT analysis with Porter’s Generic Strategy and 2020 Indonesian Cooperative Empowerment Policies a framework underexplored in existing literature. Used a qualitative descriptive approach, 57 cooperatives were analyzed via purposive sampling, focusing on digitally adaptive and policy-aligned strategies. Findings reveal distinct strategies for each type: savings and loan cooperatives require aggressive digitalization and market expansion; service cooperatives need cost leadership and operational improvements; consumer cooperatives benefit from market network diversification and e-marketing; and producer cooperatives must prioritize branding and real-time bookkeeping. These tailored strategies address gaps in prior studies, which often overlook business-type heterogeneity. The study’s implications extend to policymakers and cooperative managers, advocating for targeted interventions aligned with local conditions and national policies. Future research should evaluate the implementation efficacy of these models longitudinally and across regions to validate their adaptability.